Ideological Alignment and Evidence-Based Policy Adoption - Jorge Garcia-Hombrados; Marcel Jansen; Ángel Martínez; Berkay Özcan; Pedro Rey-Biel; Antonio Roldán-Monés (Institute of Labor Economics (IZA), 2024)
The implementation of evidence-based policies hinges on the dissemination of evidence to policymakers, a process influenced by the attributes of the sender. We conduct a country-wide RCT in which two ideologically opposite prominent think tanks, two major newspapers, and a research institution with nonsalient ideology communicate identical information about a low-cost, non-ideological, and effective policy based on published research findings to a large sample of Spanish local policymakers. We measure the impact of information directly on policy adoption and find heterogeneous effects. When the informing institution aligns ideologically with policymakers, communicating research results leads to a more than 65% increase in policy adoption compared to an uninformed control group, while informing from an opposite ideology does not lead to policy adoption. Our design also allows us to compare the impact of knowledge brokers, such as think tanks, and coverage in leading newspapers in adopting public policies. We find that, when ideologically aligned with policymakers, both are equally effective in increasing policy adoption. We propose a three-stage conceptual framework of policy adoption processes - selective exposure to information, belief updating, and policy implementation- and show that ideological alignment does not influence selective exposure to information. However, evidence from a post-intervention online experiment shows that ideological alignment affects belief updating regarding a recommended policy's effectiveness. Finally, we discuss the trade-offs between effectiveness and outreach when using ideologically aligned and nonsalient institutions to disseminate research evidence and comment on the economic impact of ideological alignment for policy implementation.
Keywords: P0; C93; D72; D78; D83; 330; evidence-based; policy adoption; ideological alignment; RCT; policy brief; media